IMPORTANCE PERFORMANCE ANALYSIS KINERJA PRODUK BATIK BATAM PELENGKAP DAYA TARIK WISATA - Agung Edy Wibowo; Tirta Mulyadi (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2022)
The purpose of this study is to determine the performance of batik products in the city of Batam. Batik products are also known as souvenir products to attract tourists. Product quality is very necessary in supporting the success of tourism in the city of Batam. Studies and research results are based on the perceptions of consumers or tourists who have had experience with those Batik products. Importance performance analysis is used in this study by measuring consumer perceptions of product attribute expectations and product performance. Test conducted use SPSS.21. The results showed that the performance of batik’s Batam was good. It can be concluded from consumer perceptions with the value of the level of conformity between consumer expectations and product performance at 98.141%, which means that 98.141% of product performance met consumer expectations. There are six indicators of product quality that met consumer expectations which are located in quadrant I, namely 1. Batam Batik has a variety of colors 2. Coloring has a philosophical meaning 3. Adequate texture quality 4. Texture softness 5. Quality raw materials 6. Imaginative trademark. And also there are five product quality indicators that need to be improved based on the priority scale which is located in quadrant IV, namely 1. Price certainty. 2. Price intervals. 3. Color variations. 4. Eco-green raw materials. 5. Packaging forms.